Mendelian Randomization Uncovers Potential Repurposable Medications for Neuropsychiatric Disorders - Xiao, Xiao; Li, Tingyu; Wang, Qiang; Gao, Linbo; Liu, Shanling; Zhang, Lin (Current Neuropharmacology, 2026)
BackgroundThe growing prevalence of neuropsychiatric disorders is becoming a major health challenge. Traditional pharmacotherapies face limitations, making drug repurposing a valuable strategy. However, high-throughput screening approaches for these conditions are scarce.MethodsThis study leveraged exposure data from the UK Biobank Neale Lab (N = 361,141) and outcome data from the FinnGen database (N = approximately 410,000) to employ Mendelian Randomization (MR) analyses and identify potential drug repurposing candidates for neuropsychiatric disorders. Sensitivity, Linkage Disequilibrium Score Correlation (LDSC), and Bayesian Colocalization (COLOC) analyses were conducted to ensure the robustness and reliability of our findings.ResultsUsing the IVW method, seven medications with negative causal associations with neuropsychiatric disorders were identified. Pregabalin, bumetanide, and prednisolone were associated with reduced anxiety (beta = -7.28, p = 4.00e-03; beta = -2.24, p = 6.00e-03; beta = -1.74, p = 2.84e-03). Vitamin B1 preparations showed an inverse association with dementia (beta = -2.47, p = 1.51e-03), Creon E/C granules with epilepsy (beta = -4.99, p = 3.91e-03), Pentasa SR 250 mg with multiple sclerosis (beta = -3.95, p = 3.83e-03), and zolmitriptan with stroke excluding subarachnoid hemorrhage (beta = -1.61, p = 6.00e-03). Sensitivity analyses confirmed these findings, whereas the LDSC and COLOC analyses provided additional support.ConclusionMR-based drug repurposing is a promising approach for the treatment of neuropsychiatric disorders. Further validation is necessary to effectively integrate these medications into clinical practice.
Keywords: genetic associations